Can we name ourselves Savimbi?: Crevice Moments and Spaces of National Reimagination in the Angolan Scouts - Auerbach, Jess; Rocha, Manuela (Kronos: Southern African Histories, 2019)
This paper presents an analysis of contemporary citizenship in one group of Angolan boy scouts in 2014. It uses Shiera El-Malik’s notion of ‘crevice moments’1 to explore specific instances of dialogue and action which reveal opening and possibility within a largely closed state that have thus far not been reflected in existing scholarly literature. The paper further considers the reasons for scouting’s popularity in post-war Angola, arguing that its military structure, religious basis, and focus on ‘adventure’ and social interactions have made it a highly desirable space for young people in a context where few opportunities exist for leisure activities. Finally, scouting enables a reconstitution of military and ideological symbols including uniforms, the socialist ideological construction of ‘the new man,’ and ‘nature’ in a way that, as one scout leader put it, is ‘fit for peace’. In this process, past, present and future are reconstituted by a movement that itself is formed and transformed in contradiction and colonial echo.